2017
DOI: 10.1073/pnas.1702472114
|View full text |Cite
|
Sign up to set email alerts
|

Origin, evolution, and global transmission of community-acquired Staphylococcus aureus ST8

Abstract: SignificanceUSA300 is a hypervirulent, community-acquired, multidrug-resistant Staphylococcus aureus clone that started to spread in the United States around 17 years ago. Many studies detected it also in South America, Europe, and the Asia-Pacific region. In this study, we show that USA300 is also circulating in sub-Saharan Africa. Locating the temporal and spatial origin of clonal lineages is important with respect to epidemiology and molecular evolution of pathogens. We show that USA300 evolved from a less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(190 citation statements)
references
References 67 publications
(111 reference statements)
5
181
0
Order By: Relevance
“…Clean reads were used for de novo assembly with SPAdes v3.6.2 (Bankevich et al, 2012). Only assemblies that harbored ≥95% of core genome (cg) MLST targets were used for further analysis as previously described (Strauß et al, 2017). If the criteria were not met, the sample was re-sequenced.…”
Section: Whole-genome Sequencing and Assemblymentioning
confidence: 99%
“…Clean reads were used for de novo assembly with SPAdes v3.6.2 (Bankevich et al, 2012). Only assemblies that harbored ≥95% of core genome (cg) MLST targets were used for further analysis as previously described (Strauß et al, 2017). If the criteria were not met, the sample was re-sequenced.…”
Section: Whole-genome Sequencing and Assemblymentioning
confidence: 99%
“…CC 8 cluster composed of two clades ST 8 (MSSA) and ST 241 (MRSA) with the two clades sharing a recent common ancestor. Studies have shown that MSSA isolates of CC 8 act as reservoirs for MRSA pending acquisition of the staphylococcal cassette [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular evolution of MRSA has been favored by horizontal gene transfer [56] and clonal dissemination of certain strains [83][84][85].…”
Section: Genetic Structure Of the Population Of S Aureusmentioning
confidence: 99%
“…In the 1990s, a new type of MRSA appeared in the USA causing infections in the community among healthy and younger people who had no history of hospital admission or medical treatment in the previous year was reported in Western Australia [70]. These types of MRSA strains were described as CA-MRSA [85,93].…”
Section: Epidemiology Of Methicillin-resistant S Aureusmentioning
confidence: 99%